Carbon Mobility in SiOC/HfO2 Ceramic Nanocomposites. Issue 7 (17th June 2013) - Nonnenmacher, Katharina; Kleebe, Hans‐Joachim; Rohrer, Jochen; Ionescu, Emanuel; Riedel, Ralf; Soraru, G.
<x xml:space="preserve">Abstract</x> Silicon oxycarbide/hafnia (SiOC/HfO2) ceramic nanocomposites were studied by transmission electron microscopy (TEM) upon isothermal annealing at 1300°C for 1–200 h. TEM investigations in conjunction with energy‐dispersive X‐ray spectroscopy (EDS) analysis revealed a pronounced reduction in the local carbon content in close proximity to internal surfaces. Such small microcracks are a consequence of the polymer‐to‐ceramic transition and, hence, are commonly formed upon thermal annealing. The profiles of the carbon content between surface and bulk were analyzed employing error functions to yield carbon diffusivities.